Comparison of geodetic slip-deficit and geologic fault slip rates reveals that variability of elastic strain accumulation and release rates on strike-slip faults is controlled by the relative structural complexity of plate-boundary fault systems - Gauriau, Judith; Dolan, James (Seismica, 2024)
Comparison of geodetic slip-deficit rates with geologic fault slip rates on major strike-slip faults reveals marked differences in patterns of elastic strain accumulation on tectonically isolated faults relative to faults that are embedded within more complex plate-boundary fault systems. Specifically, we show that faults that extend through tectonically complex systems characterized by multiple, mechanically complementary faults (that is, different faults that are all accommodating the same deformation field), which we refer to as high-Coefficient of Complexity (or high-CoCo) faults, exhibit ratios between geodetic and geologic rates that vary and that depend on the displacement scales over which the geologic slip rates are averaged. This indicates that elastic strain accumulation rates on these faults change significantly through time, which in turn suggests that the rates of ductile shear beneath the seismogenic portion of faults also vary through time. This is consistent with models in which mechanically complementary faults trade off slip in time and space in response to varying mechanical and stress conditions on the different component faults. In marked contrast, structurally isolated (or low-CoCo) faults exhibit geologic slip rates that are similar to geodetic slip-deficit rates, regardless of the displacement and time scales over which the slip rates are averaged. Such faults experience relatively constant geologic fault slip rates as well as constant strain accumulation rate (aside from brief, rapid post-seismic intervals). This suggests that low-CoCo faultsd "keep up" with the rate imposed by the relative plate-boundary condition, since they are the only structures in their respective plate-boundary zone that can effectively accommodate the imposed steady plate motion. We hypothesize that the discrepancies between the small-displacement average geologic slip rates and geodetic slip-deficit rates may provide a means of assessing a switch of modes for some high-CoCo faults, transitioning from a slow mode to a faster mode, or vice versa. If so, the differences between geologic slip rates and geodetic slip-deficit rates on high-CoCo faults may indicate changes in a fault’s behavior that could be used to refine next-generation probabilistic seismic hazard assessments.